Особливості системи захисту хімічного підприємства - Кряжич, О.І.; Захматов, В.Д. (Екологічна безпека та природокористування, 2012)
Actual ecology problem of area around chemical enterprises is timely localization and liquidation of the consequences of various accidents. The automatically system not use computer technology because of old, traditional executive system notcorrelate newsensors, analogy and command system. The combination of new computers and old executive systems isn’t effective, not ensure effective and large scale emergency actions. There propose new high effective executive system of high precisely, pulse action capable ensure timely, large scale, uniform actions – fire-fighting, localization and prevention of gas-air, vapory-air explosions, localization and liquidation of toxically clouds. It executive systems can to stop various accidents and prevent its transformations to catastrophes.